REV‐ERB agonism suppresses osteoclastogenesis and prevents ovariectomy‐induced bone loss partially viaFABP4 upregulation. Issue 6 (22nd January 2018) - Song, Chao; Tan, Peng; Zhang, Zheng; Wu, Wei; Dong, Yonghui; Zhao, Liming; Liu, Huiyong; Guan, Hanfeng; Li, Feng
ABSTRACT: REV‐ERBs (REV‐ERBα and REV‐ERBβ) are transcription repressors and circadian regulators. Previous investigations have shown that REV‐ERBs repress the expression of target genes, including MMP9 and CX3CR1, in macrophages. Because MMP9 and CX3CR1 reportedly participate in receptor activator of nuclear factor‐κB ligand (RANKL)‐induced osteoclastogenesis, we inferred that REV‐ERBs might play a role in osteoclastogenesis. In the present study, we found that the REV‐ERBα level decreased significantly during RANKL‐induced osteoclast differentiation from primary bone marrow–derived macrophages (BMMs). REV‐ERBα knockdown by small interfering RNA in BMMs resulted in the enhanced formation of osteoclasts, whereas REV‐ERBβ knockdown showed no effect on osteoclast differentiation. Moreover, the REV‐ERB agonist SR9009 inhibited osteoclast differentiation and bone resorption. Intraperitoneal SR9009 administration prevented ovariectomy‐induced bone loss; this effect was accompanied by decreased serum RANKL and C‐terminal telopeptide of type I collagen levels and increased osteoprotegerin levels. Further investigation revealed that NF‐κB and MAPK activation and nuclear factor of activated T cells, cytoplasmic 1, and c‐fos expression were suppressed by SR9009. The level of reactive oxygen species was also decreased by SR9009, with NADPH oxidase subunits also being down‐regulated. In addition, an expression microarray showed that FABP4, an intracellular lipid‐binding protein, was up‐regulated by REV‐ERB agonism. BMS309403, an inhibitor of FABP4, partially prevented the suppression of osteoclastogenesis by SR9009 through stabilizing phosphorylation of p65. To summarize, our results proved that the REV‐ERB agonism inhibited osteoclastogenesis partially via FABP4 up‐regulation.—Song, C., Tan, P., Zhang, Z., Wu, W., Dong, Y., Zhao, L., Liu, H., Guan, H., Li, F. REV‐ERB agonism suppresses osteoclastogenesis and prevents ovariectomy‐induced bone loss partially via FABP4 upregulation. FASEB J. 32, 3215–3228 (2018). www.fasebj.org